Analysis and evaluation of standardization in acoustics in Poland - CZARNECKI, Stefan (Archives of Acoustics, 1977)
Industrial development and the consequent intensification of the process of urbanization presents an irreversible menace to man's environment, his work-place, his home and his rest. Amongst the numerous hazards for man, the Polish law and national industrial health service include excessive noise and mechanical vibrations which occur in the environment.